(untitled) (Journal of Veterinary Medicine and Animal Production, 2022)
Trypanosoma evansi infection is the most important disease of Camel in the Sudan. The objective of this research was to give an account of the Camel current situation in the two study areas. However, Comparison between conventional (parasitological), serological (Card agglutination test) and molecular (PCR) techniques in diagnosis of T. evansi in camels, were carried out from a total of 600 natural hosts (Camels). The obtained results showed that PCR has higher sensitivity and specificity (90%) than others techniques. This work has provided information on the prevalence of the disease; therefore, certain steps should be taken for treatment and designing rational Trypanosomiasis control program as well as it will be useful for any epidemiological study. The Questionnaires results showed the current situation of Camels in Al-Showak and Al-Obeid areas, concerning the migration of animal, movement pattern, sings of clinical diagnosis, other diseases, other grazing animals, veterinary services, problems facing the owners and their solutions. To improve the health and productivity of Camels in Sudan, these findings should be taken in consideration by the authorities.